Handbook of Energy Governance in Europe 2020
DOI: 10.1007/978-3-319-73526-9_22-1
|View full text |Cite
|
Sign up to set email alerts
|

Energy Governance in the Republic of Poland

Abstract: Governance of energy transitions has become an issue of growing prominence in the social sciences and in political practice. Examining the understudied case of the "least climate ambitious" European Union Member State, Poland, the investigation demonstrates that it has a highly centralized energy system in decisionmaking. Employing a state-led governance approach, which includes an overlap between political and administrative actors in terms of personal and organizational capacity, the analysis highlights the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…On the basis of the analysis of changes in greenhouse gas emissions (Table 1) and the share of individual energy sources, it can be concluded that the policies from the Polish government since the beginning of economic and political changes (1989) have been ineffectual in this respect. The Polish government, as stated by Zoll [53], the main actor in the process of energy transformation and decarbonisation, is simply ineffective. Additionally, to some extent, it has become a hostage of mining trade unions for many years, opposing the reduction of hard coal mining in the country, which was also indicated by Brauers and Oei [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the analysis of changes in greenhouse gas emissions (Table 1) and the share of individual energy sources, it can be concluded that the policies from the Polish government since the beginning of economic and political changes (1989) have been ineffectual in this respect. The Polish government, as stated by Zoll [53], the main actor in the process of energy transformation and decarbonisation, is simply ineffective. Additionally, to some extent, it has become a hostage of mining trade unions for many years, opposing the reduction of hard coal mining in the country, which was also indicated by Brauers and Oei [14].…”
Section: Discussionmentioning
confidence: 99%
“…The rich literature on energy transformation in Poland most often addresses issues and problems related to mining and energy industry based on hard coal [47][48][49][50], the problems of nuclear energy [51] and of energy based on RES [52] and matters of political challenges posed by energy transformation for Poland, both in the internal dimension [53] and Poland's obligations as a member of the European Union [54,55]. The input factors include historical conditions, the current structure of energy produced (dominance of fossil resources) and alternative visions of transformation (RES, nuclear energy and offshore wind energy).…”
Section: The Energy Policy Of Poland Until 2040 (Pep2040)mentioning
confidence: 99%
“…On the other hand, this ambition has been constantly bedevilled by continuing conflict between different blocs of Member States, namely those in favour of more stringent climate action and those who prefer policies that stress security of the energy supply as well as independence from key actors, such as Russia (see Knodt, 2018;Zoll, 2020). As a result, the Member States have generally been hesitant to harden climate policy monitoring, and thus have often pushed in the opposite direction, i.e.…”
Section: The Member Statesmentioning
confidence: 99%
“…With more selfconfidence and bolstered by a rising anti-European sentiment at home, many governments of the Visegr ad Group opposed strong regulation on renewable energies (and especially binding, national-level targets), arguing that the Member States should stay in full control of choosing their energy sources (Interview August 2017); (even though some differences do emerge in this group on renewables; see Cetkovi c and Buzog any 2019). In particular, countries such as Poland were keen to retain control over their national energy mix to exploit their national coal resources and ensure the security of their supply (Solorio and Bocquillon 2017), lest they become dependent on Russian oil and gas, a situation that continues to be highly politically unattractive for the Polish people, especially in light of the recent Ukrainian gas crises (Zoll 2020). In our interviews, Polish representatives also stressed the need to retain flexibility because renewable energy expansion tends to be nonlinear and expansion costs tend to decrease over time (Interview March 2018).…”
Section: Actor Configurationmentioning
confidence: 99%